Mobilizing on the extreme right : Germany, Italy, and the United States - Caiani, Manuela 1976- (Oxford University Press, 2012)
The extreme right and social movement studies: an introduction -- Methodological choices in the analysis of the extreme right: research design and research methods -- The context of the extreme right -- Networking online -- The action repertoires of the radical right: violence and beyond -- Framing the "Us": identity building in the extreme right -- Fighting modernity: the extreme right and conservative values -- Racism: old and new forms? -- The other "no globals": right-wing discourses on globalization -- The extreme right, populism, and politics -- The extreme right: a conclusion.